Implementation of a damage calculation in a numerical wheel-rail contact simulation / Christian Buzzi, Andreas Dutzler and Martin Leitner - Buzzi, Christian; Dutzler, Andreas; Leitner, Martin (Smart Manufacturing Research Institute (SMRI), 2021)
Railways can transport cargo and persons a great distance. The combination of high axle loads, and the rigid wheels and rails made of steel results in high stresses at the wheel-rail contact. These high stresses cause rolling contact fatigue. To prevent and to forecast the rolling contact fatigue, the knowledge of the stresses and their effect on the local damage are important. One possible way to achieve results of the stresses is based on a finite element analysis. The calculation of the rolling contact fatigue is conducted subsequently. This paper will present one possibility to implement the damage calculation into a finite element software and use the post-processing to enable a fast assessment of rolling contact fatigue on the surface and the adjacent volume of a rail.